Validation of the age, neutrophil to lymphocyte ratio, C reactive protein score on 28 day mortality in the National COVID cohort collaborative - Benjamin J. Sines; Kunal K. Jakharia; Chih-Huan Lu; Leslie Appleton; Colleen Rice; William A. Fischer; Shannon M. Wallet; G. Stephen DeCherney; Jason R. Mock; M. Bradley Drummond (Scientific Reports)
Abstract Identifying patients at high mortality risk can improve outcomes in SARS-CoV-2 pneumonia (COVID-19). We validate a prognostic model for mortality in patients hospitalized with COVID-19 receiving dexamethasone using a retrospective multi-centered study. This is a retrospective cohort study using the National COVID Cohort Collaborative (NC3) including 9,708 adult patients admitted for COVID-19 who received dexamethasone within 24 h of admission and remained hospitalized for 72 h. Previous work from a single-center cohort informed selection of prognostic variables including Age, day 3 neutrophil-lymphocyte Ratio, and day 3 C-reactive protein level (ARC Score). Variables from the development cohort were analyzed in a training cohort, and the resulting model was tested in a validation cohort. Age and day 3 measures of the neutrophil-lymphocyte ratio and C-reactive protein level were included in a logistic regression model to predict 28-day mortality. The 28-day mortality in this patient population was 15.4%. The area under the curve for the ARC model was 0.77 (95% confidence interval, 0.74–0.79). The Age, neutrophil-lymphocyte Ratio, and C-reactive protein (ARC) score identifies COVID-19 patients with a high risk of mortality within 28 days of hospitalization using clinical information on day 3 of hospitalization. ARC scores perform well across all variants of concern.